2017
DOI: 10.5152/tud.2017.24478
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance treatment with gemcitabine have a promising activity on metastatic bladder cancer survival

Abstract: Objective: To investigate the effects of gemcitabine maintenance treatment on survival in patients with metastatic bladder cancer. Material and methods:Gemcitabine maintenance monotherapy was administered following the standard platinum-gemcitabine therapy in patients with metastatic bladder cancer. Patients who had responded to standard treatment received maintenance gemcitabine therapy as 1000 mg/m 2 on days 1 and 8 every three weeks until progression or development of unacceptable toxicity. The following cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In our study, the visceral metastasis was not statistically significant prognostic parameter was as in Kus and Aktas (14) study (P=0.482). On the contrary, Muto et al (12) study demonstrated that the presence of visceral metastases (P=0.007), the success of initial chemotherapy (P=0.018), and GEM maintenance therapy (P<0.001) were all statistically significant predictors of DSS.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…In our study, the visceral metastasis was not statistically significant prognostic parameter was as in Kus and Aktas (14) study (P=0.482). On the contrary, Muto et al (12) study demonstrated that the presence of visceral metastases (P=0.007), the success of initial chemotherapy (P=0.018), and GEM maintenance therapy (P<0.001) were all statistically significant predictors of DSS.…”
Section: Discussioncontrasting
confidence: 43%
“…The maintenance treatment in our study, the median (range) of number of cycles was (1-12)cycles with median dose of cycle (1000-1800mg) while Muto et al (12) the median was (2-49 ) cycles with median dose of cycle (500-1795mg), Kus and Aktas (14) the Median 7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) cycles with median dose of cycle (500-1800mg) and Lehmann et al (15) reported administrating 41 cycles of GEM maintenance monotherapy with cumulative total dose of gemcitabine 88.500mg.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Therefore, the development of new therapies is still desirable. Gemcitabine, a nucleoside antimetabolite that inhibits DNA synthesis, is one of the most often used anticancer drugs in the treatment of BTCC [ 4 , 5 ]. However, the development of chemoresistance for gemcitabine has become one of the most important reasons for treatment failure and has resulted in relapse, metastasis or patient death [ 6 ].…”
Section: Introductionmentioning
confidence: 99%